Solvent-Directed Morphological Transformation in Covalent Organic Polymers - Cao, Xuan Thang; Kumar, Subodh; Nemec, Ivan; Kopp, Josef; Varma, Rajender S. (Frontiers in Materials, 2022)
Synthesis of bi-functional covalent organic polymers in two distinctive morphologies has been accomplished by simply switching the solvent from DMF to DMSO when 1, 3, 5-tribenzenecarboxyldehyde and 2, 5-diaminobenzene sulfonic acid were reacted via schiff base condensation reaction to afford covalent organic polymers (COPs) encompassing flower (F-COPDMF) and circular (C-COPDMSO) type morphologies. Chemical and morphological nature of the synthesized COPs were compared by characterization using TEM, SEM, XRD, FT-IR, and XPS analysis techniques. Besides diverse morphology, both the polymeric materials were found to comprise similar chemical nature bearing protonic acid –SO3H and Lewis base –C=N functionalities. Subsequently, both the COPs were evaluated for the synthesis of hydroxymethylfurfural (HMF) by the dehydration of fructose to investigate their morphology dependent catalytic activity.